UV/Chlorination of sulfamethazine (SMZ) and other prescription drugs: kinetics, transformation products and insights into the combined toxicological assessment. Issue 3 (28th January 2022) - Yan, Xiaoshu; Chen, Han; Lin, Tao; Chen, Wei; Xu, Hang; Tao, Hui
ABSTRACT: The UV/chlorination of three prescription drugs, sulfamethazine (SMZ), gemfibrozil (GEM) and antipyrine (ANT) were studied by the investigation of kinetics, transformation products and combined toxicological assessment. The degradation followed pseudo-first-order kinetics, with half-lives significantly affected by chlorine dosage, without being greatly influenced by pH value and bromide concentration. Based on the Frontier Orbital Theory, the structures of products by hydroxylation or chlorine substitution were proposed and the transformation pathways were introduced, with two, two and one never-before-reported products identified for SMZ, GEM and ANT, respectively. Compared to the results of the experiments with artificial water sample, the degradation kinetics of the three prescription drugs was observed with a prolonged half-lives in both Yangtze River and Taihu Lake water, suggesting that aromatic containing transformation products (TPs) may also exist in UV/chlorine treated natural waters. The results of combined toxicity on E. coli showed that the antagonism effect predominated in most binary and ternary combinations. However, the synergistic toxicity of combinations at low concentrations of prescription drugs subjected to UV/chlorine should be cautioned, which was more close to the natural concentration of prescription drugs in waters. GRAPHICAL ABSTRACT: UF0001